Seismic Performance of Self-Centering Frame Structures with Additional Exterior Wall Panels Connected by Flexible Devices - Caiyan Zhang; Xiao Lai; Weihang Gao (Buildings)
To address the issue of deformation mismatch between the exterior wall panels and the resilient frame structure under large deformations, two novel flexible devices (FDs) with different working principles are proposed in this paper. These FDs enable the exterior wall panels to achieve cooperative deformation with frame columns or beams under horizontal loads, thus improving the seismic performance of the frame structure with additional exterior wall panels. This study begins by explaining the specific design thought of the FDs based on examining the deformation characteristics of frame structures. Then, a series of low-cycle loading tests are conducted on frame specimens to demonstrate the effectiveness of the FDs. The experimental results indicate that the FDs can improve the interaction between the exterior wall panels and the main frame, reduce plastic damage to the wall panels, and increase the peak load-bearing capacity of the overall structure by approximately 17–21%. In addition, a refined finite element modeling method for the proposed FDs is presented using the ABAQUS software, providing a basis for further research on frame structures with additional exterior wall panels.